Islamic Views on Riba in Muamalah Based on the Qur'an Hadith - Susandi, Adi; Romli, Muhammad; Rahman, Adun (Yayasan Mentari Madani, 2024)
Riba refers to the provision of additional value given by exceeding the nominal amount of a loan at the time of repayment. The interest rate is determined based on a certain percentage charged to the borrower. In Arabic, riba means excess or addition (az-ziyadah). In Islam, riba is strictly prohibited. The Qur'an explicitly declares that riba is forbidden because it is considered harmful and creates injustice in economic transactions. This prohibition aims to maintain social balance and protect parties involved in transactions from economic exploitation. This study employs a qualitative method with a library research approach. This approach aims to explore the views of scholars and authoritative Islamic sources, such as the Qur'an, hadith, and fiqh literature. Based on the findings from various reliable sources, Islamic law clearly states that riba is haram. This prohibition is supported by theological and ethical arguments emphasizing the importance of justice and blessings in all aspects of muamalah. Thus, riba is not only viewed as an economic issue but also as a moral and spiritual concern that must be avoided by Muslims